4. Optimalisasi peran aktif siswa dalam pendidikan dengan model pembelajaran partisipatif untuk meningkatkan hasil belajar mata pelajaran pendidikan jasmani olahraga dan kesehatan siswa Kelas VI SDN Blega 3 Kecamatan Blega Kabupaten Bangkalan - ., Supadmi (JURNAL WAHANA PENDIDIKAN DASAR, 2017)
Based on the background of the above problems, it can be stated formulation of the problem is as follows: Is there an increase in student learning outcomes through mastery learning model partisipatifpada subjects of Physical Education and Health at Blega VISDN Class 3 District of Blega Bangkalan? This research was conducted in Class VI SDN Blega 3 Blega District of Bangkalan, Class VI student number as many as 32 students, the condition of specificity allows the student ability levels and absorption of these students vary greatly. The researcher is Professor of Physical Education and Health at SDN Blega 3 Blega Subdistrict Bangkalan which is a primary school achievement and favorite school in Bangkalan who have long-term educational development prospects are good. Based on studies that have been done, then the following chapters will be presented the conclusions in the study of this action. The conclusions are consistent with the formulation of the problem and the purpose of research it can generally be stated that results for students Class VI SDN Blega 3 District of Blega Bangkalan, can improve through learning by using Learning Participatory Based on the research findings, we can conclude that the learning model uses Participatory learning can improve student achievement and can enhance students' skills in solving problems in the Basic Competence Know how denial of drug use in the subject of Physical Education and Health at the students of SDN Blega 3 Blega Subdistrict Bangkalan.